A Global Survey of Reproductive Specialists to Determine the Clinical Utility of Oxidative Stress Testing and Antioxidant Use in Male Infertility - Agarwal, Ashok; Finelli, Renata; Selvam, Manesh Kumar Panner; Leisegang, Kristian; Majzoub, Ahmad; Tadros, Nicholas; Ko, Edmund; Parekh, Neel; Henkel, Ralf; Durairajanayagam, Damayanthi; Colpi, Giovanni M; Cho, Chak Lam; et al. (The world journal of men's health, 2021)
PURPOSE: The use of antioxidants is common practice in the management of infertile patients. However, there are no established guidelines by professional societies on antioxidant use for male infertility. MATERIALS AND METHODS: Using an online survey, this study aimed to evaluate the practice pattern of reproductive specialists to determine the clinical utility of oxidative stress (OS) testing and antioxidant prescriptions to treat male infertility. RESULTS: Responses from 1,327 participants representing 6 continents, showed the largest participant representation being from Asia (46.8%). The majority of participants were attending physicians (59.6%), with 61.3% having more than 10 years of experience in the field of male infertility. Approximately two-thirds of clinicians (65.7%) participated in this survey did not order any diagnostic tests for OS. Sperm DNA fragmentation was the most common infertility test beyond a semen analysis that was prescribed to study oxidative stress-related dysfunctions (53.4%). OS was mainly tested in the presence of lifestyle risk factors (24.6%) or sperm abnormalities (16.3%). Interestingly, antioxidants were prescribed by 85.6% of clinicians, for a duration of 3 (43.7%) or 3-6 months (38.6%). A large variety of antioxidants and dietary supplements were prescribed, and scientific evidence were mostly considered to be modest to support their clinical use. Results were not influenced by the physician's age, geographic origin, experience or training in male infertility. CONCLUSIONS: This study is the largest online survey performed to date on this topic and demonstrates 1) a worldwide understanding of the importance of this therapeutic option, and 2) a widely prevalent use of antioxidants to treat male infertility. Finally, the necessity of evidence-based clinical practice guidelines from professional societies is highlighted.